Design and implementation of a 1GHz CMOS resonator utilizing surface acoustic wave - Nordin, Anis Nurashikin; Zaghloul, Mona E. (2006)
The design and fabrication of an integrated 1GHz surface acoustic wave (SAW) resonator is described in this paper. The SAW resonator was fabricated using a combination of CMOS plus surface micromachining techniques. Utilizing the minimum feature size of the available 0.6 micron AMI CMOS process, the periodic distance of the interdigitated fingers of the SAW resonator was designed to create an ultra high frequency resonator of 1.15 GHz. Measurements and characterization of the fabricated resonator were performed and used as a basis to develop a two-port equivalent circuit model. To complement the resonator, a Pierce oscillator circuit was designed in CMOS to create a frequency synthesizer capable of generating frequencies up to 1.15GHz without the complexity of a phase-locked-loop (PLL) circuit